Exploring Factors of Working Capital Credit Distribution: Interest Rates, Deposits and Customer Perception - Muhammad Anas; La Diu Samiu; Linda Ayu Oktoriza; Muhammad Al Faridho Awwal; Ariawan (Jurnal Informatika Ekonomi Bisnis, 2023)
This study examines the impact of interest rates, customer deposits, and customer perception of the Five C's of Credit on the disbursement of working capital loans in Bank Perkreditan Rakyat (BPRs). A quantitative approach was utilized, and data were collected from 108 BPR customers in Gorontalo through an online questionnaire using Google Forms. The collected data were analyzed using the SPSS technique. The findings indicate that all three variables have a significant influence on the disbursement of working capital loans in BPRs. Interest rates, customer deposits, and customer perception of the Five C's of Credit play crucial roles in the credit evaluation process and loan allocation decisions in BPRs. The results of the analysis demonstrate that these variables collectively account for 58.7% of the variation in the disbursement of working capital loans. This highlights the significance of considering these factors when determining credit allocation in BPRs. However, it is important to acknowledge the limitations of this study. Other variables not included in this research could also impact credit disbursement in BPRs. Future studies could explore additional factors and expand the sample size to enhance the generalizability of the findings. The findings offer valuable insights for BPRs in formulating effective lending policies and practices to address the financing needs of businesses. By doing so, BPRs can contribute to the economic growth and development of the region.